How Have Firms Fared in Times of COVID-19 in Addis Ababa? : Evidence from Eight Rounds of High-Frequency Phone Surveys - Wieser, Christina; Abebe, Girum; Asfaw, Adamsu (World Bank, Washington, DC, 2021)
The COVID-19 pandemic and its negative economic effects create a need for timely data and evidence to help monitor and mitigate the social and economic impacts of the crisis. To monitor the impacts of the COVID-19 pandemic and related containment measures on formal firms in Ethiopia and inform the policy response, the World Bank, in collaboration with the government, is implementing a high-frequency phone survey of firms (HFPS-F). The HFPS-F interviews a sample of firms in Addis Ababa every three weeks for a total of eight survey rounds. This high-frequency follow-up allows for a better understanding of the effects of and responses to the COVID-19 pandemic on firm operations, hiring and firing, and expectations of future operations and labor demand in order to better tailor and implement interventions and policy responses and monitor their effects